Potential rainwater harvesting suitable land selection and management by using GIS with MCDA in Ebenat District, Northwestern Ethiopia - Mulualem Asfaw Ejegu; Endalkachew Sisay Yegizaw (Journal of Degraded and Mining Lands Management, 2020)
Rainwater harvesting (RWH) is the way to reduce the effects of mid-season dry spells and drought, which often reduce crop yields. Geographic information system (GIS) with multi-criteria decision making (MCDA) is a powerful tool to identify and solve spatial problems like the identification of the suitable site of RWH. Sentinel image, soil, metrological row data, geological data, and digital elevation model (DEM) data were the source of a dataset to undertake the preprocessing, manipulation, and analysis the suitable site identification by using GIS and remote sensing spatial analysis. More than seven parameters where identified based on an extensive literature review which is land use/land-cover, soil textural, rainfall, lineament, slope, runoff density and curve number, distance from settlement and road. The multi-criteria decision-making method was used for weight value estimation of each criterion and finally, the rainwater harvesting suitability map was generated. The potentially suitable site was grouped into four levels of suitability, which accounts in hectare 3,620, 16,0618, 69,867, and 14,010 ha of highly suitable, moderately suitable, less suitable, and restricted respectively from the total area coverage of 248,115 ha respectively.